Characterization of ash from sugar palm [Arenga Pinnata (Wrumb) Merr.] fibre for industrial application - Aliyu, Isah; Mohd Sapuan, Salit; Zainudin, Edi Syams; Rashid, Umer; Mohamed Zuhri, Mohd. Yusoff; Yahaya, Ridwan (Taylor and Francis Group, 2023)
Sugar palm (Arenga Pinnata) fiber is abundant in Malaysia which necessitates its utilization as a source of agricultural waste for industrial development. This paper aims at characterizing the sugar palm fiber to explore its silica content as a potential renewable material. The sugar palm fiber was carbonized, and the ash obtained was characterized via X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), energy dispersive spectroscopy (EDS) and field emission scanning electron microscope (FESESM). The presence of amorphous silica (SiO2) with an average particle size of 41.25 nm was revealed by X-ray diffraction. Fourier transform infrared spectroscopy indicated the presence of functional groups such as silane and siloxane groups, and thermogravimetric analysis and differential scanning calorimetry identified the main degradation stages of the sugar palm fiber ash, and the decomposition of hemicellulose, lignin, cellulose, and carbonate to other oxides. The energy dispersive spectroscopy of the sugar palm fiber ash confirmed silica to be of the highest amount than other elements. Sugar palm fiber ash has been found as a possible silica substitute and a prospective industrial resource.